The impacts of the Turkish government's conspiratorial framing of the Gezi Park protests - Nefes, T (Routledge, 2017)
What happens when a prime minister frames a momentous protest as a foreign conspiracy? The Turkish government’s reaction to the Gezi Park protests, a reaction centred on a conspiracy theory about an ‘interest rate lobby,’ provides a unique case to explore the impacts of conspiracy theories about big-scale protests. Relying on quantitative and qualitative content analysis of online users’ responses to the government’s conspiracy theories, I discuss the socio-political significance of this conspiratorial rhetoric. The findings demonstrate that (1) the previous political views of online users predict their responses to conspiracy theories, and (2) the users’ comments were centred on their perceptions of the government. These show that people tend to interpret the conspiracy theories in line with their political values and interests, and, accordingly, that the government’s conspiratorial frames concerning the protests seem to have contributed to the political fragmentation by enhancing the division between the Justice and Progress Party (AKP) supporters and opponents.